Penegakan Hukum Judi Online Chip Domino Yang Dilakukan Oleh Wilayatul Hisbah Ditinjau Dari Qanun No. 13 Tahun 2003 Tentang Maisir - Ade Soraya (An-Nasyr, 2023)
Enforcement of online gambling by Wilayatul Hisbah as stipulated in Article 15 Paragraph (3) in Qanun Number 13 of 2003 concerning Maisir (gambling) states that "In carrying out the coaching function, Wilayatul Hisbah officials who find perpetrators of finger maisir can give warnings and guidance in advance to offender before handing them over to investigators. From this article it can be interpreted that the Wilayatul Hisbah has the authority to arrest the perpetrators of maisir. Even though it has been regulated in such a way, both in statutory regulations, Aceh Qanun Number 13 of 2003, as well as Qanun No. 6 of 2014 concerning Jinayah Law. The Wilayatul Hisbah law enforcement apparatus is still vacillating in carrying out its functions, because there are two investigators in the Maisir Qanun, namely Wilayatul Hisbah investigators (PPNS) and Police investigators. Eradication of gambling is not something that can be easily eliminated, it is necessary to have legal regulations that take strict action against the perpetrators of gambling crimes. Regulations for gambling were originally regulated in Article 542 of the Criminal Code, but based on the provisions stipulated in Article 2 paragraph (4) of Law no. 7 of 1974 concerning Controlling Gambling, has been amended in the criminal provisions in Article 303 bis of the Criminal Code.